2003
DOI: 10.1159/000070770
|View full text |Cite
|
Sign up to set email alerts
|

Results of Magnetic Resonance Imaging Assessment, Acoustic Analysis, Phonatory Function and Perceptual Rating of Glottic Insufficiency before and after Fat Augmentation: Correlated with Subjective Rating

Abstract: Autogenous fat augmentation has been proven effective in the treatment of glottic insufficiency (GI) using both subjective and objective methods of evaluation. However, no information is available in published research regarding the effectiveness and predictability of value parameters with regard to patients’ perceptions and concerns. This article retrospectively examines the correlation between subjective and objective examinations and subjective ratings (SRs) in patients with presbylaryngis (n = 14) and sulc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 13 publications
(20 reference statements)
0
3
0
1
Order By: Relevance
“…Autologous fat injection is known to be safe [ 21 ], but the long-term (> 1 year) benefits are less consistent [ 12 , 19 , 22 , 23 ]. The effectiveness of autologous fat injection in patients with non-paralytic glottic insufficiency caused by atrophy with or without sulcus has been studied to a lesser extent, with generally positive subjective results [ 19 , 22 24 ]. Chen et al reported excellent results in 62.5% of their patients based on subjective patient ratings, together with an overall significant improvement in the perceptual rating of grade, roughness, and breathiness, and videolaryngostroboscopic rating [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Autologous fat injection is known to be safe [ 21 ], but the long-term (> 1 year) benefits are less consistent [ 12 , 19 , 22 , 23 ]. The effectiveness of autologous fat injection in patients with non-paralytic glottic insufficiency caused by atrophy with or without sulcus has been studied to a lesser extent, with generally positive subjective results [ 19 , 22 24 ]. Chen et al reported excellent results in 62.5% of their patients based on subjective patient ratings, together with an overall significant improvement in the perceptual rating of grade, roughness, and breathiness, and videolaryngostroboscopic rating [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Injectable materials include synthetic substances such as calcium hydroxylapatite (CaHA) and Gelfoam, as well as autologous fat and collagen 3 , 11 . Gelfoam, autologous fat, and collagen all show reabsorption once injected; thus reinjection is often necessary 3 , 6 , 7 10 , 12 . As with medialization thyroplasty, foreign body reactions can also be a concern.…”
Section: Discussionmentioning
confidence: 99%
“…3,11 Gelfoam, autologous fat, and collagen all show reabsorption once injected; thus reinjection is often necessary. 3,6,[7][8][9][10]12 As with medialization thyroplasty, foreign body reactions can also be a concern. In both augmentation injection and medialization thyroplasty, material is generally added to the paraglottic space or musculature, not the superficial lamina propria of the vocal fold; thus adhesion in the vocal fold is not corrected.…”
Section: Discussionmentioning
confidence: 99%
“…Abb. 4).Autologes Fettgewebe hat gute elastische Eigenschaften und ist sehr gut verträg-lich[18]. Es wird vom Patienten vor der Injektion durch Liposuktion oder Exzision aus der Bauchwand gewonnen.…”
unclassified